A world of artist journal pages - Sokol, Dawn DeVries (New York : STC Craft, 2015)
Showcase of more than 1,000 art journaling pages by 230 artists from 30 countries.--
"By nature, art journaling is a private activity. But when Dawn Sokol's first book, 1000 Artist Journal Pages, broke the fourth wall and shared the work of artists all over the United States, it created a ripple of inspiration throughout the art journaling community. In this much-anticipated follow-up, Sokol features more than 1,000 new, captivating pages, this time--by popular demand--from artists across the globe. Lists of techniques and materials used for each page, plus behind-the-scenes interviews, give readers a glimpse inside the minds of new and established artists, making this a stimulating compilation sure to inspire beginners and seasoned art journalers alike."--
"A Melanie Falick book."
Includes index.
Featured artists: Julia Dean, Nathalie Nayer, Sarah Bunker, Jeanette House, Ines Seidel, Hagit Azoulay-Rozanes, Natasha White, Janne Robberstad, Elena Sevrina, Bea Mahan, Brittany Baier, Ashley Fielden, Lisa Cheney, Brian Kasstle, Courtney White, Missy Dunaway.
Keywords: Scrapbook journaling; Doodles